Two new species of the genus Cyanopenthe Nikitsky, 1998 (Coleoptera, Tetratomidae) from southwest China - Qiaoqiao Ji; Guodong Ren (ZooKeys, 2019)
The genus Cyanopenthe Nikitsky, 1998 is first recorded from mainland China. Two new species, C. granulata sp. nov. and C. hirtiscutellara sp. nov., are described and illustrated. This genus is redefined, and an updated key to the known species is presented.